Fabrication of anatase titanium dioxide nanotubes by electroless deposition using polycarbonate for separate casting method - Boehme, M.; Fu, G.; Ionescu, E.; Ensinger, W. (Nano-Micro Letters, 2010)
Titanium dioxide nanotubes (TNTs) were prepared by electroless deposition using ion track etched polycarbonate templates. The ion tracks were prepared to the desired diameter of the TNTs outer diameter. Titanium dioxide nanotubes with a diameter of minimum 80 nm having a wall thickness of minimum 10 nm can be fabricated using this method. To achieve nanotubes with thin walls and small surface roughness the tubes were generated by a several steps procedure under aqueous conditions at nearly room temperature. The presented approach will process open end nanotubes with well defined outer diameter and wall thickness. Using this method TNT arrays up to 109 tubes per cm2 having a tube length up to 30 μm can be produced, single tubes are also possible. The structural properties of the grown TNTs were investigated by using various analytical techniques, i.e. scanning electron microscopy (SEM), energy dispersive X-ray fluoresence spectrometer (EDX), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Raman spectroscopy and Photoluminescence.